Outcome of patients with surgical extraction of lower third molar in teaching hospital - Shah, Arun Kumar; Gautam, Shailesh; Singh, Harender (Journal of Chitwan Medical College, 2021)
Background: Surgical extraction is frequently associated with considerable post-operative swelling, pain and limited mouth opening. These sequelae are caused by physiological inflammatory response to trauma. This study was carried out to evaluate the post-operative outcome after surgical extraction. Methods: An observational study was carried out involving 141 patients. After taking proper history and performing clinical examination, diagnosis of impacted lower third molar was confirmed by Orthopantomogram (OPG). Paired T-test, independent t-test and Anova test was applied to check the level of significance. A p value less than .05 was considered statistically significant. Results: The study revealed that the gender factor predicted pain on Day 3 and Day 7 (p < 0.05). Gender predicted mouth opening at Day 3 (p < 0.05). Swelling was not affected by gender on any day. Pain was affected by age at Day 3 and Day 7. swelling and mouth opening was affected by age at Day 3 only. Operating time affected the swelling, pain and mouth opening on both 3rd and 7th day. Conclusions: Based on the findings of the present study, short-term outcomes of third molar surgery (swelling, mouth opening and pain) differed depending on the characteristics of the patient (age and gender) and operating time. However, due to the observational character of the study, the results should be interpreted with caution. Further studies are supposed to be carried out on relations between preoperative findings and short-term outcomes of third molar extractions.